Whose Comfort? - Yonson Ahn (Singapore : World Scientific Publishing Co Pte Ltd, 2019)
"This book examines the system of military 'comfort women' in World War II created and maintained to provide sexual servitude to its armed forces by Japan during World War II. The ways in which body, sexuality and identity are deployed in the maintenance of colonial/nationalist power, patriarchal relations and ethnic hierarchies are explored in this work. To achieve this objective requires examining issues of body politics, power, femininity and military masculinity, all of which are entangled in the context of the 'comfort women' system. This volume relies mainly on presonal narratives, including testimonies and life histories of Korean 'comfort women' victims/survivors and Japanese veterans obtained from interviews that the author conducted as well as from previously published testimonies."-- Back cover
Keywords: Comfort women; Sex crimes; Service, Compulsory non-military